PROSES IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA PUTUSSIBAU - M. Bessiar (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2020)
AbstractThe fundamental problem of the research is the policy implementation program of waste management in Kapuas Hulu is not as expected. Therefore, The responsibility of waste management program must be handled by all of the local government and the other stakeholders. The research aim is to describe and analyze the policy process of the implementation program. The research type is a survey research by the descriptive model. There are four Kelurahan in the research, namely Kelurahan Putussibau Kota, Kelurahan Hilir Kantor, Kelurahan Kedamin Hulu and Kedamin Hilir. The research result shows that the compliance of the implementers is in the Standard Procedure Operational. But, in the legal aspect is not optimally performed. The recommendation of this research is the local government, such as Dinas Lingkungan Hidup, Perumahan Rakyat dan Kawasan Permukiman, must be immediately issued the local regulation on waste management. Besides, the local government must plan and establish the derivative regulation of the local regulation. .Key words : The policy implementation program of waste management , Compliance, Whats Happening